PENGARUH PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI, BUDAYA ETIS ORGANISASI DAN KESESUAIAN KOMPENSASI TERHADAP FRAUD (Studi Empiris Pada Bank BUMN Di Kota Pekanbaru) - Frans, Colondam; Riska, Natariasari; Alfiati, Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The level of fraud in Indonesia, which is still a big and widespread problem, is corruption. Banking statistics that indicate fraud in Indonesia in the last two years, namely in 2017, there were 57 banks that were indicated as a fraud. Meanwhile, in 2018 there were 36 indications of fraud until the third quarter. This study aims to determine the effect of Internal Control, Compliance with Accounting Rules, Organizational Ethical Culture, and Compensation Suitability for Fraud. The population in this study were employees of people's business loans (KUR) and financial employees of state-owned banks in the city of Pekanbaru. The questionnaires in this study were distributed to 50 state-owned banks in the city of Pekanbaru. The sampling technique used was incidental sampling. Incidental sampling is the determination of the sample based on chance, that is, anyone who accidentally / incidentally meets the researcher can be used as a sample, if it is considered that the person who happened to be met is suitable as the data source. The results of hypothesis testing are: first, Internal Control has an effect on fraud. Second, adherence to accounting rules affects fraud. Third, Organizational Ethical Culture affects fraud. The fourth Compensation suitability affects fraud.Keywords: Fraud, Internal Control, Compliance with Accounting Rules, Organizational Ethical Culture and Compensation Suitability